Effectiveness of Virgin Coconut Oil in The Provision of Injury Pressure Sores Stroke Patients: Systematic Review - Sya'bani, Nurul Indah; Hafid, Muhammad Anwar; Putra, Andi Budiyanto Adi (Universitas STRADA Indonesia, 2020)
Background: VCO is an oil made from fresh coconuts and processed naturally or do not require heating and do not add other chemicals. The fatty acids contained in the VCO has the added benefit of making your skin soft. VCO is effectively applied as a moisturizer to the skin so that it can improve skin hydration and promotes healing of the skin. Decubitus is damage to the skin caused by friction or pressure on the skin located bony section.Purpose: This literature review aimed to determine the effectiveness of the VCO in reducing the risk of decubitus sores.Method: This research method Quantitative descriptive approach Systematic Review through some journals that are relevant to this article. This research article search by using keywords 1